2023
DOI: 10.3390/molecules28062496
|View full text |Cite
|
Sign up to set email alerts
|

Improved Phenolic Profile, Sensory Acceptability, and Storage Stability of Strawberry Decoction Beverages Added with Blueberry Decoctions

Abstract: Blueberries are rich in polyphenols, anthocyanins, and proanthocyanidins; however, they are expensive. In contrast, strawberries have a lower cost and are rich in ellagitannins. Therefore, a strawberry–blueberry blend decoction could produce a low-cost beverage with a rich and diverse phytochemical profile. In this study, we developed three berry-based beverages: blend strawberry–blueberry (SBB), strawberry (SB), and blueberry (BB). The polyphenol profile of the beverages was characterized by UPLC-ESI-Q-ToF MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, soy-based and black bean-based yogurt alternatives contained significant amounts of ferulic and p-coumaric acids and research by Fan et al (2019) [56] demonstrated that these acids act as effective copigments that enhance the stability of anthocyanins residues in blackberry-wine fermentation. Sotelo-González et al ( 2023) [57] reported that polyphenols in the strawberry-blueberry blend beverage could exert a copigmentation effect, reducing the rate of anthocyanin degradation during storage.…”
Section: Changes In Anthocyanin Content During Storage Of Strawberry ...mentioning
confidence: 99%
“…Furthermore, soy-based and black bean-based yogurt alternatives contained significant amounts of ferulic and p-coumaric acids and research by Fan et al (2019) [56] demonstrated that these acids act as effective copigments that enhance the stability of anthocyanins residues in blackberry-wine fermentation. Sotelo-González et al ( 2023) [57] reported that polyphenols in the strawberry-blueberry blend beverage could exert a copigmentation effect, reducing the rate of anthocyanin degradation during storage.…”
Section: Changes In Anthocyanin Content During Storage Of Strawberry ...mentioning
confidence: 99%